The implementation of risk management plans and programs : A case study of Syabas Sdn. Bhd. - Arbak, Salwani (Universiti Utara Malaysia, 2007)
This is an exploratory study on Implementing Risk Management Plans and Programs which focusing on one case study that had been conducted at Syarikat Bekalan Air Selangor Bhd (SYABAS).The main aims of this study is to identify whether SYABAS do practice its Risk Management Plans and Programs and also to identify in detail the risk management process suggested by AS/NZS 4360 model.This study found that does not fully practiced and utilized Risk Management Process as suggested by this model.This study gives some recommendations and suggestions to Syabas and other utilities companies on how to be more efficient in implementing its risk management plans and programs.